THE RELATIONSHIP OF EDUCATIONAL LEVEL ON PATIENT COMPLIANCE IN TAKING ANTI-HYPERTENSION MEDICATION INMENTENG MITRA AFIA GENERAL HOSPITAL - Nuniek Setyo Wardani; Setiyadi, Agung; Desfa Fitri , Melissa; Manurung, Sondang; Parulian, Intan (Journal of Nursing and Midwifery Sciences, 2024)
In Indonesia, the estimated number of hypertension cases in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. The aim of this study was to determine the relationship between education level and patient compliance in taking antihypertensive medication at the Menteng Mitra Afia General Hospital. This type of research is quantitative research with a cross-sectional research design and using a questionnaire. The population in this study was 95 respondents who suffered from hypertension. This research uses a purposive sampling technique. The variables in this research are gender, age, education level and compliance. The Chi-Square test results were obtained with a value of p = 0.002 < α (0.05), so it was significant, so Ho was rejected and Ha was accepted, meaning that there was a relationship between the level of education and patient compliance in taking antihypertensive medication.Keywords: Hypertension, Education Level, Medication Compliance.